Classroom Management in Foreign Language Education: An Exploratory Review (2018)
This review examines studies in the area of classroom management in foreign language education. It is organized into three large areas: The first area focuses on the distinctive characteristics of foreign language instruction that are more likely to impact classroom management in foreign language classes. The second area provides a description of classroom management issues that foreign language teachers usually encounter in their practice; and the third area centers on the different alternatives to reduce the negative impact of classroom management on foreign language classes. Conclusions suggest a need for more research particularly on the relationship between classroom management and aspects such as target language use and teaching methods.